1998
DOI: 10.1255/jnirs.133
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of near Infrared Spectroscopy for Evaluation of Microbial Nitrogen Content of in Sacco Feed Residues and Duodenal Digesta of Sheep

Abstract: This study aimed to estimate by near infrared (NIR) spectroscopy the microbial nitrogen content (MN) of feed residues from in sacco degradability trails and duodenal digesta of sheep. NIR spectra from 50 samples of duodenal digesta, and from in sacco residues-110 samples of alfalfa hay and 38 samples of maize silage were obtained using an NIRSystems 4250 spectrophotometer. The microbial nitrogen (MN) content of part of the alfalfa hay in sacco residues (78 samples) was calculated from the percentage of 15 N en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Particularly, the 2148-2200 nm band has been demonstrated as useful to predict protein in forage (Andrés et al 2005) and agricultural products (Shenk et al 2001). Similar to our results, Atanassova et al (1998) found absorption bands in 1720-1891 nm, 1930-2090 nm and 2090-2500 nm wavelength regions useful to predict microbial-N content of in sacco feed residues and duodenal digesta of sheep.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Particularly, the 2148-2200 nm band has been demonstrated as useful to predict protein in forage (Andrés et al 2005) and agricultural products (Shenk et al 2001). Similar to our results, Atanassova et al (1998) found absorption bands in 1720-1891 nm, 1930-2090 nm and 2090-2500 nm wavelength regions useful to predict microbial-N content of in sacco feed residues and duodenal digesta of sheep.…”
Section: Discussionsupporting
confidence: 90%
“…For free-browsing ungulates, like moose, it is legitimate to expect heterogeneity in chemical fractions of lignin in the diet due to spatio-temporal variation in the type, availability and maturity of the feed. Anyway, the model parameters for the prediction of microbial-N and lignin concentrations in our study are comparable or even better than those observed for duodenal digesta (microbial-N: R 2 = 0.88, SEcv = 3.80; Atanassova et al 1998) and other herbage (Lignin: R 2 adj = 0.66, SEP = 7.18 g kg −1 DM; Andrés et al 2005).…”
Section: Discussionsupporting
confidence: 75%
“…5 NIR has already been shown to be able to monitor biological processes and has been used for the better understanding of the kinetics, the rate and extent of degradability of different forages in rumen. 6,7 Therefore, in this paper we report on and evaluate the applicability of a specially-designed and developed fibre optic for the on-line NIR measurement of rumen fluid in milking cows.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, differences in microbial flora could translate to some exposure-resistant differences in rodent fNIR-spectra. For instance, diaminopimelic acid (DAPA), a marker of gut microbe derived N in feces (Karr-Lilienthal et al, 2004) has good NIRS calibrations (Atanassova, Todorov, Djouvinov, Tsenkova, & Toyoda, 1998), and has been found to retain stable concentrations in exposed deer feces (Kamler et al, 2003). In summary, rodent species identification is likely to rest on a multitude of fecal constituents, many of which link with phylogenetic distance (Ley et al, 2008; Zierer et al, 2018), and have varying resistance to exposure and decay.…”
Section: Discussionmentioning
confidence: 99%